Differences in the prevalence of hospitalizations and utilization of emergency outpatient services for ambulatory care sensitive conditions between asylum-seeking children and children of the general population: a cross-sectional medical records study (2015) - Lichtl, Célina; Lutz, Thomas; Szecsenyi, Joachim; Bozorgmehr, Kayvan (BMC health services research, 2017)
Hospitalizations for ambulatory care sensitive (ACS) conditions are established indicators for the availability and quality of ambulatory care. We aimed to assess the differences between asylum-seeking children and children of the general population in a German city with respect to (i) the prevalence of ACS hospitalizations, and (ii) the utilization of emergency outpatient services for ACS conditions.